Toward Elicitation of Bioactive Secondary Compounds with Environmentally Sound Plant Treatments: Insight into the Balance between Photosynthetic Primary and Kaempferol Accumulating Secondary Metabolism Using Young Soybean Plants - H. H. Ratnayaka; S. Boue; T. Dinh; S. B. Le; R. Cherubin (Cutting-edge Research in Agricultural Sciences Vol. 10, 2021)
Environmentally sound plant treatments that can impose mild physiological stress and elicit bioaccumulation of useful phytochemicals such as kaempferols are limited. We tested ABA foliar application, 100 or 200 µM, and two types of leaf wounding, piercing or hole punching in young greenhouse-grown soy plants. Leaf gas exchange and A/Ci response, \(φ\)PSII, pigments and antiradical activity were measured using the same leaf and kaempferols were measured in the leaf above. ABA 200 µM-treated plants had \(≥\)20% less gas exchange and 17% less ETR, but greater Vcmax and Jmax compared with control. They had 55% and 100% more stomatal limitation to Pnet and \(φ\)PSII, respectively, than the control. Leaf-wounded plants showed the lowest stomatal limitation to either Pnet or \(φ\)PSII. Leaf piercing increased chlorophylls 39% and carotenoids 38% compared with the control. Six kaempferols quantified were found to be mono-, di- and triglycosides. Each leaf treatment increased total kaempferol yield ranging from 42% in ABA 100 µM to 68% in ABA 200 µM treatment compared with control. In general, kaempferol yields were positively correlated to Pnet in ABA 100 µM-treated plants and to gs in ABA 200 µM-treated plants but negatively correlated to Pnet in leaf-pierced plants. Results of this study show that appreciable increase in kaempferol yield and thus phytochemical or nutritional quality of soy leaves is achievable with environmentally friendly foliar treatments. ABA application and wounding affected the association between photosynthetic primary metabolism and kaempferol accumulation differently. Both ABA application and wounding are promising leaf treatments for eliciting kaempferol accumulation in young soy leaves.